The Finite Family \(L\)-Lipschitzian Suzuki-Generalized Nonexpansive Mappings - Suanoom, Cholatis; Sriwichai, Kittikorn; Klin-Eam, Chakkrid; Khuangsatung, Wongvisarut (Communications in Mathematics and Applications, 2019)
In this paper, we propose and analyze a \(L\)-Lipschitzian Suzuki-generalized nonexpansive mapping on a nonempty subset of a hyperbolic space and prove \(Δ\)-convergence theorems and convergence theorems for a \(L\)-Lipschitzian Suzuki-generalized nonexpansive mapping in a hyperbolic space.